Evaluation of a computational strategy to model transitory injection in rotating detonation combustors - Hellard, Pierre; Gaillard, Thomas; Davidenko, Dmitry (Frontiers in Aerospace Engineering, 2023)
The efficiency of a Rotating Detonation Combustor (RDC) strongly depends on the transitory injection process of fresh reactants in the combustion chamber: poor propellant mixing induces losses of combustion efficiency and consequently low detonation speed and unstable detonation propagation. Moreover, dilution of fresh reactants with burnt gases during injection increases the deflagration losses and decreases the pressure gain provided by the detonation. Numerical simulation can help design an efficient injector to reduce these losses. In this study, the modeling strategy previously proposed by ONERA to simulate the transitory injection process is applied to two existing experimental RDC (from Nagoya University and TU Berlin). The computational domain represents only one injection element, convenient for a parametric study at low computational cost. A custom initial condition is used to model the expansion process of burnt gases past a detonation wave. The initial condition parameters are discussed and a method is proposed to correctly set them. The TU Berlin RDC is studied in more detail: mixing efficiency up to 70% is obtained, and 5% of deflagration losses are computed from the simulation. Based on the numerical results, detonation speed was evaluated at various distance from the injection plane taking into account heterogeneities of the fresh mixture. The measured speed lies within the predicted range.